OP0310 A Deletion at Adamts9-MAGI1 Locus is Associated with Psoriatic Arthritis Risk. (9th June 2015) - Cañete, J.; Pinto, J.A.; Gratacόs, J.; Queirό, R.; Ferrándiz, C.; Fonseca, E.; Montilla, C.; Torre-Alonso, J.C.; Puig, L.; Pérez Venegas, J.J.; Fernández Nebro, A.; Fernández, E.; et al.
Abstract : Background: Copy-Number Variants (CNV) have been associated to the risk to develop multiple autoimmune diseases. Objectives: Our objective was to identify CNVs associated with the risk to develop Psoriatic Arthritis (PsA) using a genome-wide analysis approach. Methods: A total of 835 PsA patients and 1, 498 controls were genotyped for CNVs using the Illumina HumanHap610 BeadChip. The most significant CNV associations with PsA risk were independently tested in a sample of 1, 133 PsA patients and 1, 831 controls. In order to test for the specificity of the variants with PsA etiology, we also analyzed the association to a cohort of 822 purely cutaneous psoriasis (PsC) patients. Results: A total of 165 common CNVs were identified in the GWAS. We found a highly significant association of an intergenic deletion between ADAMTS9 and MAGI1 genes (p=0.00014). Using the independent patient and control cohort we validated the association between ADAMTS9-MAGI1 deletion and PsA risk (p=0.032). Using next-gen sequencing we characterized the associated deletion. Finally, analyzing the PsC cohort we found a lower frequency of the deletion compared to PsA (p=0.0088) and similar to that of controls (p>0.3). Conclusions: The GWAS for CNVs has identified a new deletion associated with PsA risk and which is also differential from PsC risk. Disclosure of Interest: None declared